Data Science for Dummies - Pierson, Lillian (Tantor Audio, 2019)
Jobs in data science abound, but few people have the data science skills needed to fill these increasingly important roles. Data Science For Dummies is the perfect starting point for IT professionals and students who want a quick primer on all areas of the expansive data science space. With a focus on business cases, the book explores topics in big data, data science, and data engineering, and how these three areas are combined to produce tremendous value. If you want to pick-up the skills you need to begin a new career or initiate a new project, listening to this book will help you understand what technologies, programming languages, and mathematical methods on which to focus. While this book serves as a wildly fantastic guide through the broad, sometimes intimidating field of big data and data science, it is not an instruction manual for hands-on implementation. Here's what to expect: &#9679 Provides a background in big data and data engineering before moving on to data science and how it's applied to generate value &#9679 Includes coverage of big data frameworks like Hadoop, MapReduce, Spark, MPP platforms, and NoSQL &#9679 And more It's a big, big data world out there-let Data Science For Dummies help you harness its power and gain a competitive edge for your organization.
Online resource; title from title details screen (OverDrive, viewed September 26, 2019)
Keywords: Information technology; Information retrieval; Databases; Data mining; Information Storage and Retrieval; Data Mining; Technologie de l'information; Recherche de l'information; Exploration de données (Informatique); information technology; information retrieval; COMPUTERS; General; Downloadable audio books; Audiobooks; Livres audio